The Analysis of Computer Based Test (CBT) Implementation: A Phenomenological Study - Fitriyah, Sofiyatul; Laily, Nujmatul (Journal of Accounting and Business Education, 2018)
The purpose of this research is to describe the planning, implementation, and obstacles in implementing CBT. It is a qualitative research using phenomenological approach. The subjects of this research are Accounting teachers and students in Vocational High School 1 Turen. The method for collecting the data are interview and documentation. The validation of data was conducted by the triangulation of sources. Data analysis using Miles and Huberman technic. The research shows that (1) Planning Computer Based Test (CBT) for midterm and final test includes the formulation of objectives, selecting officers, preparing the system, facilities, and infrastructures needed for the test, socialization for teachers and students, preparing the test items and CBT simulation. (2) The implementation of the computer-based test (CBT) for midterm and final test is the responsibility of Proctor and technician. Teachers role during the CBT only as the supervisor of the test and assess the result. (3) Problems in the implementation of CBT are the trouble of internet connection, electricity, and the chance for the student to browse easily. There are some strategies to overcome those problems such as giving a clear instruction as the supervisor of CBT, preparing enough genset, empowering wifi connection and server for the stability of internet connection.